La Saga de Camelia la Texana. La mujer en el narco y en el narcocorrido - Salvador Bernabéu Albert (Conserveries Mémorielles)
In recent decades, women have become more present in the world of drug trafficking, coping with various functions within criminal organizations, despite not achieving high positions of power, armored by a strongly male chauvinist structure. In the first part of the paper, we analyzed the role of females in cartels, from retail trade to money laundering, and, in more recent times, more violent roles such as that of sicarias or torturers. In the second one, we study the reflection of these activities in the narcocorridos, musical genre preferred by the narcos to praise their heroes and feats. It also addresses the most recent changes in the diffusion and consumption of this music and its new compositions, increasingly aggressive and sanguinary, reflecting a country captive for extortion, corruption and indiscriminate violence.